PsycEXTRA Dataset 2000
DOI: 10.1037/e501882009-397
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian View of Covariation Assessment

Abstract: When participants assess the relationship between two variables, each with levels of presence and absence, the two most robust phenomena are that: (a) observing the joint presence of the variables has the largest impact on judgment and observing joint absence has the smallest impact, and (b) participants' prior beliefs about the variables' relationship influence judgment. Both phenomena represent departures from the traditional normative model (the phi coefficient or related measures) and have therefore been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 39 publications
(68 reference statements)
6
65
1
Order By: Relevance
“…However, when the materials concerned features for which they possessed no relevant background beliefs (genotype and personality type), people were relatively insensitive to rarity information presented in the scenario. McKenzie and Mikkelsen (2007) have extended these results to a covariation detection task where they observed that people's perception of the information carried by the joint presence or joint absence of two possibly correlated variables was affected by whether absence or presence of the possibly correlated variables was rare. However, such rarity effects were only observed for concrete materials for which people were likely to have had pre-existing beliefs about rarity.…”
Section: Discussionmentioning
confidence: 72%
“…However, when the materials concerned features for which they possessed no relevant background beliefs (genotype and personality type), people were relatively insensitive to rarity information presented in the scenario. McKenzie and Mikkelsen (2007) have extended these results to a covariation detection task where they observed that people's perception of the information carried by the joint presence or joint absence of two possibly correlated variables was affected by whether absence or presence of the possibly correlated variables was rare. However, such rarity effects were only observed for concrete materials for which people were likely to have had pre-existing beliefs about rarity.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, common arithmetic word problem errors can be better simulated using deficient text comprehension strategies than deficient logico-mathematical strat egies (Dellarosa, 1986). Similar arguments concerning the neces sity of investigating how participants interpret decision-making queries in experiments have been put forth by Oaksford and Chater (1994) and McKenzie and Mikkelsen (2007).…”
Section: The Confusability Of Causal Power and Predictive Judgment Qumentioning
confidence: 76%
“…Models of Bayesian inference dictate that low probability events are especially informative (e.g., McKenzie & Mikkelsen, 2007) and, in a similar fashion, social psychological research on person perception suggests that rare behaviors lead to stronger traitbased attributions (Ditto & Jemmott, 1989;Fiske, 1980;Jones & Davis, 1965;Kelley, 1967). Indeed, participants did report that the cat-beater had performed a more uncommon act than the woman-beater, M = 2.00, 95% CI [1.71, 2.90], p b .001.…”
Section: Resultsmentioning
confidence: 96%